Perancangan Website Sebagai Media Promosi Dan Informasi - Penda Sudarto Hasugian (STMIK Pelita NUsantara, 2018)
Along with the current technological developments, technology is widely used as a means of promotion and information, especially in the field of websites that currently become a medium of information that offers a variety of ease in presenting information. Speed and comfort is a positive value of the internet. Websites are more accessible to people in different regions just by using the internet. One of them in terms of product marketing a business, the website can be a means of promoting, marketing and convey effective and efficient information to the community. Ves Boutique is a business engaged in the field of fashion. In promoting and marketing, the boutique is still using less efficient way of them through brochures, banners in front of the store. The boutique can utilize the website as a media promotion and information to advance the boutique and show that the boutique has a good quality in terms of promotion. In designing the website as a media campaign and information on the ves boutique consists of two pages including, admin page and main page. Consumers can access without having to login first. This is done to facilitate the consumer. In this website, consumers can place a product order directly without having to visit the boutique. This website is designed using PHP and MySQL as the database. Keywords: Website, Media Promotion and Information, Php and MySql